Teknologi Mobile Untuk Pengelolaan Data Siswa Praktik Kerja Lapangan - Nandang Hermanto (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
Praktik Kerja Lapangan (PKL) is one of the activities in the vocational teaching and learning process which takes place in a direct business environment, the main purpose of implementing PKL is to introduce students to the world of work. The implementation of PKL at SMK Ma'arif NU 1 Sumpiuh is carried out for 6 months which is divided into 2 implementation activities, namely 3 months odd semester and 3 months even semester. The purpose of this study is to provide a suggestion to facilitate the process of recording PKL student data both in odd and even periods. In addition, the system proposal also provides details on the quota data for street vendors and bridges if in the second stage of PKL implementation there are students who move street vendors. The PKL application has gone through the system functional testing phase and has been running according to the needs of the PKL activity process. The technology used in this study uses a mobile so that all activities both from the school, committee and students can be monitored in real time by all related parties.